Analisis Bibliometrik tentang E-Procurement sebagai Bagian dari E-Government: Evolusi Topik, Dinamika Riset, dan Implikasi Kebijakan - Nugraha, Diva; Sri Kartini, Dede (Universitas Serang Raya, 2025)
The transformation of public governance through digitalization has positioned e-Procurement as a key component in the implementation of e-Government. As a technology-based procurement system, e-Procurement not only enhances procurement efficiency and effectiveness but also strengthens public accountability and transparency. This study aims to map the global scholarly development and dynamics of e-Procurement using a bibliometric approach. The data were drawn from 1,322 scientific publications indexed in the Scopus database during the period 2010–2024 and analyzed using VOSviewer software. The analysis identified five main thematic clusters reflecting the evolution of research directions: digital business efficiency, transparent governance, utilization of data analytics and artificial intelligence, challenges in technology adoption, and the integration of digital innovations such as blockchain. The findings reveal a shift in research focus from technical aspects toward strategic technological integration and multidisciplinary approaches. This study concludes that e-Procurement has evolved into an instrument of digital governance reform that is adaptive, innovative, and collaborative. Therefore, strengthening institutional capacity, enhancing cross-sector and cross-country synergy, and developing data-driven policies are essential to support sustainable and inclusive e-Procurement implementation. Keywords: e-Procurement, e-Government, bibliometrik